The secret life of the American musical : how Broadway shows are built - Viertel, Jack; Kagan, Abby; Sarah Crichton Books (yhtiö) (Sarah Crichton Books, Farrar, Straus and Giroux, 2016)
"Americans love musicals. Americans invented musicals. Americans perfected musicals. But what, exactly, is a musical? In [this book], Jack Viertel takes them apart, puts them back together, sings their praises, marvels at their unflagging inventiveness, and occasionally despairs over their more embarrassing shortcomings. In the process, he invites us to fall in love all over again by showing us how musicals happen, what makes them work, how they captivate audiences, and how one landmark show leads to the next"--Dust jacket flap.
Keywords: Musicals : United States : History and criticism; Musicals : United States : Analysis, appreciation; musiikkianalyysi; musikaalit; musikaler; musikanalys; Yhdysvallat; Förenta staterna